2012
DOI: 10.1002/anie.201107906
|View full text |Cite
|
Sign up to set email alerts
|

Inverse and High CO2/C2H2 Sorption Selectivity in Flexible Organic–Inorganic Ionic Crystals

Abstract: Highly selective CO2 sorption and inverse CO2/C2H2 sorption selectivity (4.8 at 278 K, 100 kPa) were achieved with an organic–inorganic ionic crystal. The key for the high affinity toward CO2 is the combination of structural flexibility and strong binding sites (K+) characteristic of organic–inorganic ionic crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 61 publications
4
89
0
1
Order By: Relevance
“…The assignments of μ 3 ‐OH are based upon bond valence sum analyses, and three samarium ions are joined by nine carboxylate groups and a μ 3 ‐OH to form the trinuclear [Sm 3 (OH)(COO) 9 ] cluster (Figure a). Although many similar clusters have been observed in other compounds, the [Ln 3 (OH)(COO) 9 ] cluster is rare in the Ln‐MOFs reported to date. Each ligand is linked to five samarium atoms through three different carboxylate groups.…”
Section: Resultsmentioning
confidence: 99%
“…The assignments of μ 3 ‐OH are based upon bond valence sum analyses, and three samarium ions are joined by nine carboxylate groups and a μ 3 ‐OH to form the trinuclear [Sm 3 (OH)(COO) 9 ] cluster (Figure a). Although many similar clusters have been observed in other compounds, the [Ln 3 (OH)(COO) 9 ] cluster is rare in the Ln‐MOFs reported to date. Each ligand is linked to five samarium atoms through three different carboxylate groups.…”
Section: Resultsmentioning
confidence: 99%
“…[6,7] Therefore,i ti sm ore facile to remove the water of hydration from Cs + ,t hereby allowing the ion to more easily enter and diffuse through the crystal lattice.T he coulomb interaction between Cs + and POM oxygen atoms in I-red was estimated to be À310 kJ mol À1 with an average Mulliken charge of À0.7e [31] in aqueous media, and acombined Cs + and O 2À ionic radius [4] of 3.1 , which may be large enough to compensate for the dehydration energy of Cs + (306 kJ mol À1 ). [7] Thed iffusion coefficient (Figure 2b) [32] may have contributed to diffusion of Cs + between the closed pores.…”
mentioning
confidence: 99%
“…[7] In many large-scale industrial oxidation processes,C Oi s produced, which has to be separated from N 2 for chemical processing. Size-related sieving, [2d, 9] gate-opening [10] in flexible microporous frameworks,o rr eversible chemical binding [9c, 11] are the main mechanisms for discrimination. [8] This separation process is challenging owing to the similar physical properties of both gases.For separation of CO,ahighly selective but nevertheless reversible adsorption is needed.…”
Section: Microporousmaterialswereinitiallydominatedbyzeolitesmentioning
confidence: 99%
“…[8] This separation process is challenging owing to the similar physical properties of both gases.For separation of CO,ahighly selective but nevertheless reversible adsorption is needed. Size-related sieving, [2d, 9] gate-opening [10] in flexible microporous frameworks,o rr eversible chemical binding [9c, 11] are the main mechanisms for discrimination. To date CO is mostly separated by chemisorption on transitionmetal ions such as Cu +, which however requires ac ostintensive,endergonic release of CO. [12] Sato et al for example recently reported as elf-accelerating CO sorption in as oft nanoporous material with selective CO adsorption on aCu 2+ -PCP.…”
mentioning
confidence: 99%